Intervention with self-suggestive procedures for self-efficacy and pain control - Pires, Ana F. (2013)
Introduction – Pain is the predominant complaint in many medical diseases and carries several implications for the patient1-4. The present study aimed to evaluate the effectiveness of a self-suggestive intervention, as a complement to medical treatment, in the patient's self-efficacy and pain control. Methodology – For this aim, 205 adult patients suffering from pain were randomized into two groups that received different interventions during 12 weeks: the IAS group received a self-suggestive intervention and the ISAS group received an intervention without self-suggestion. The two groups were compared regarding the changes in self-efficacy and pain control over the 12 weeks. Results and discussion – The results showed a statistically significant increase of these variables in the IAS group but not in the ISAS group, suggesting the efficacy of the self-suggestive intervention. This study represents an important contribution to the clinical practice of patients suffering from pain.